Oogenesis and Spermatogenesis of the Triploid Black Tiger Shrimp, Penaeus monodon - Saearlee, Muthita; Semchuchot, Wanita; Vanichviriyakit, Rapeepun; Withyachumnarnkul, Boonsirm; Pongtippatee, Pattira (Trends in Sciences, 2024)
Triploidy (3n) induction of Penaeus monodon was performed separately by Australian and Thai groups of researchers 14 years ago, incidentally at the same period. The Australian group employed the chemical induction method, while the Thai group the cold shock one, and both groups obtained 3n P. monodon in their attempts. The success has led to several studies on the physiology of the 3n P. monodon, including growth, survival and reproductive functions. Both groups reported sterility of the 3n shrimp. The Australian group reported defected oogenesis and spermatogenesis of the 3n shrimp examined at subadult stage. Since the evaluation of the reproductive functions should be performed at the adult stage of the animals, we, therefore, performed in-depth studies on oogenesis and spermatogenesis of adult 3n P. monodon induced by cold shock. The studies include gross observation of the ovary, light (LM) and transmission electron (TEM) microscopy and image analysis of sex cells. The ovary of the 3n P. monodon females could not develop to full-maturation and their gonadosomatic index (GSI) was significantly lower than that of the 2n shrimp. Oogenesis of the 3n females proceeded from oogonia to cortical rod oocytes, but with significantly lower percentage than that of the 2n shrimp. The GSI of the 3n males was significantly lower than that of the 2n shrimp. Their spermatogenesis, however, proceeded normally from spermatogonia to spermatozoa, but with low density of spermatozoa in the seminiferous tubule and vas deferens, and none in the terminal ampoule. The average nuclear area of the 3n spermatozoa was significantly lower than that of the 2n shrimp as well. Altogether, these results suggest that 3n P. monodon induced by cold shock had defect in both oogenesis and spermatogenesis, probably more in quantity than in quality. HIGHLIGHTS Oogenesis and spermatogenesis of the triploid black tiger shrimp, monodon, induced by cold shock were studied. The study found abnormalities in the spermatogenesis, but not oogenesis, of the triploid P. monodon induced by cold shock. It may be concluded that triploidy condition of P. monodon induced by cold shock affects meiotic, but not mitotic activity of the sex cells. GRAPHICAL ABSTRACT